“Philosophical Paradigms in The Fight Against Corruption Today: Problems and Solutions - Khidirov Khoshim Ibodullaevich; Tursunova Dildora Bahromovna (Genius Journals, 2022)
The article deals with the fight against the scourge of corruption, which is currently considered a negative scourge in the world, the measures, problems and solutions that need to be taken in this regard
Keywords: World; Corruption; paradigm; Estonia